Effect of G40 plasticizer on the properties of ternary blends of biodegradable PLA/PBS/G40 - Runglawan Somsunan (2019)
© 2019, The Polymer Society, Taipei. The ternary blends poly(lactic acid) (PLA), poly(butylene succinate) (PBS) and poly(ester adipate) (G40) were prepared and studied their properties by melt mixing method. It was found that the G40 influences the properties of PLA/PBS blends and the interfacial adhesion of PLA and PBS, which was confirmed by scanning electron microscopy and an increase in the transparency. Tensile strength and modulus were found to decrease with increasing G40 content, which were in the range of 10–55 MPa and 200–1500 MPa respectively. The elongation at break of the blends increased when adding 5% of G40, indicating more flexibility when incorporate with G40. However, for higher amount of G40 than 10%, the elongation at break starts to decrease as G40 increased. This corresponds to thermal properties tests which showed that the glass transition temperature of the blends decreased as the amount of G40 increased. In addition, the water vapor permeability of the blends was also enhanced 50–200% by the incorporation of 5–15% of G40. In conclusion, it was confirmed that G40 has the potential to be a suitable plasticizer for PLA/PBS blends. This study provides useful guidelines for the future design and application of PLA/PBS/G40 blends for use as novel bioplastics.